Development of a flow‐cell coupled to dynamic SPME technique for automated measurement of fragrance emission from fabric. (9th July 2022) - Zou, Jian; Zhang, Shiling; Duan, Shuyu; Winniford, Bill
Abstract: A novel automated flow‐cell coupled dynamic solid‐phase microextraction (SPME) method was developed to study the emission of volatile fragrance compounds from fabric samples in a microchamber. Calibration curves were developed with the liquid‐inner tube diffusion‐film‐emission (LIFE) vial technique to quantify the gas‐phase concentration of nine significant volatile fragrance compounds. The linearity range for the various volatile fragrance compounds ranged from 0.001 to 37.9 mg/m 3 . The limit of quantitation (LOQ) for each fragrance compound was determined as 3.6–12.1 μg/m 3 . Using this method, we obtained comprehensive emission curves of target volatiles to quantify the volatile emission profiles of fabric samples. Compared with traditional chamber test method procedures, this work provides a novel and automated method to allow the online monitoring of the emission of various volatiles from multiple samples in one experiment. The repeatability and sensitivity of the method are comparable to or better than existing offline techniques. Abstract : A novel automated flow‐cell coupled dynamic solid‐phase microextraction (SPME) method was developed to study the emission of volatile fragrance compounds from fabric samples in a microchamber. Using this method, we obtained comprehensive emission curves of target volatiles to quantify the fragrance emission profiles of fabric samples.